2018
DOI: 10.4103/sjg.sjg_551_17
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility for celiac disease is highly prevalent in the Saudi population

Abstract: Background/Aim:To determine the frequency of celiac disease (CD)-predisposing human leukocyte antigen (HLA)-DQ genotypes in the Saudi population, where the prevalence of CD is 1.5% as recently reported in a mass screening study.Patients and Methods:In a cross-sectional population-based study, a total of 192 randomly selected healthy school children (97 females, mean age 10.5 ± 2.2 years, all negative for tissue transglutaminase-IgA) were typed for DQA1 and DQB1 genes by polymerase chain reaction sequence–speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
1
14
0
1
Order By: Relevance
“…34 Compared with our study, higher frequencies in the review by Alarida were reported from Mexico (28.3%), Turkey (22%), North India (15.6%) and Iran (12%). 34 Our findings indicate that more than half (51.6%) of the Ethiopian population is carrying any of the DQ2.5, DQ2.2 and DQ8 haplotypes, which was comparable with the Swedish references (55.9%) and other previous studies performed on the general population in Australia (55.9%), 37 Iran (58%), 18 Saudi Arabia (52.7%), 25 but slightly higher than Brazil (43.7%) 38,39 and Denmark (47.7%). 40 Although this study is the largest HLAgenotyped Ethiopian population to date, it is limited by the fact that children included in the present study were enrolled from only one region and therefore may not represent the whole population in Ethiopia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…34 Compared with our study, higher frequencies in the review by Alarida were reported from Mexico (28.3%), Turkey (22%), North India (15.6%) and Iran (12%). 34 Our findings indicate that more than half (51.6%) of the Ethiopian population is carrying any of the DQ2.5, DQ2.2 and DQ8 haplotypes, which was comparable with the Swedish references (55.9%) and other previous studies performed on the general population in Australia (55.9%), 37 Iran (58%), 18 Saudi Arabia (52.7%), 25 but slightly higher than Brazil (43.7%) 38,39 and Denmark (47.7%). 40 Although this study is the largest HLAgenotyped Ethiopian population to date, it is limited by the fact that children included in the present study were enrolled from only one region and therefore may not represent the whole population in Ethiopia.…”
Section: Discussionsupporting
confidence: 90%
“…HLA risk classifications for celiac disease are summarized in Table 1 and were stratified according to having very low risk to very high risk as described previously. 8,21,[25][26][27]…”
Section: Study Populationmentioning
confidence: 99%
“…HLA-DQ genes are responsible for the immunological recognition of cells. The produced proteins of HLA-DQ2 and HLA-DQ8 genes form a functional protein complex-the antigen-binding dimer (DQαβ), when affixing to peptides outside the cell, recognizes them as foreign or own proteins, triggering an immune response in the first case [34,35]. These genes can cause an autoimmune disease in the case of inadequate immune response: for example, an inadequate response to gluten proteins, which cause the inflammation that damages body organs and tissues and lead to the signs and symptoms of celiac disease.…”
Section: Genes Associated With Food Intolerancesmentioning
confidence: 99%
“…Of course, other concomitant environmental exposures and epigenetic mechanisms are supposed to be critical to determine which individuals will become celiac within a much larger HLA-predisposed population. [2] Currently, the global prevalence of CD worldwide has been estimated to be around 1% and resulted to be significant and increasing even in areas of the world where CD was previously thought to be negligible [3][4][5] As regards CD in Asia, several clinical data from Iran, Turkey and Israel suggested a prevalence similar to Europe. Moreover, a significant prevalence of CD has been widely described in the Indian subcontinent, especially in those regions where the dietary exposure to gluten is important.…”
Section: Introductionmentioning
confidence: 99%